Implementation of a community transport strategy to reduce delays in seeking obstetric care in rural Mozambique - Amosse, Felizarda; Boene, Helena; Kinshella, Mai-Lei Woo; Drebit, Sharla; Sharma, Sumedha; Makanga, Prestige Tatenda; Valá, Anifa; Magee, Laura A.; Dadelszen, Peter von; Vidler, Marianne; Sevene, Esperança; Munguambe, Khátia (Global Health Science and Practice, 2022)
Introduction: Delays due to long distances to health facilities, poor road infrastructure, and lack of affordable transport options contribute to the burden of maternal deaths in Mozambique. This study aimed to assess the implementation and uptake of an innovative community-based transport program to improve access to emergency obstetric care in southern Mozambique.